The X‐ray structure of human calbindin‐D28K: an improved model. Issue 10 (5th October 2018) - Noble, James W.; Almalki, Rehab; Roe, S. Mark; Wagner, Armin; Duman, Ramona; Atack, John R.
Abstract : The X‐ray structure of human calbindin‐D28K, a calcium‐buffering protein that is highly expressed in the central nervous system, is reported. Abstract : Calbindin‐D28K is a widely expressed calcium‐buffering cytoplasmic protein that is involved in many physiological processes. It has been shown to interact with other proteins, suggesting a role as a calcium sensor. Many of the targets of calbindin‐D28K are of therapeutic interest: for example, inositol monophosphatase, the putative target of lithium therapy in bipolar disorder. Presented here is the first crystal structure of human calbindin‐D28K. There are significant deviations in the tertiary structure when compared with the NMR structure of rat calbindin‐D28K (PDB entry2g9b ), despite 98% sequence identity. Small‐angle X‐ray scattering (SAXS) indicates that the crystal structure better predicts the properties of calbindin‐D28K in solution compared with the NMR structure. Here, the first direct visualization of the calcium‐binding properties of calbindin‐D28K is presented. Four of the six EF‐hands that make up the secondary structure of the protein contain a calcium‐binding site. Two distinct conformations of the N‐terminal EF‐hand calcium‐binding site were identified using long‐wavelength calcium single‐wavelength anomalous dispersion (SAD). This flexible region has previously been recognized as a protein–protein interaction interface. SAXS data collected in both the presence and absence of calcium indicate that there are no large structural differences in the globular structure of calbindin‐D28K between the calcium‐loaded and unloaded proteins.